HIV infection and sexual behaviour in primary and secondary infertile relationships: a case–control study in Kigali, Rwanda. Issue 1 (18th September 2010) - Dhont, Nathalie; Muvunyi, Claude; Luchters, Stanley; Vyankandondera, Joseph; De Naeyer, Ludwig; Temmerman, Marleen; Wijgert, Janneke van de
Abstract : Objective: To compare the prevalence of sexually transmitted infections (STIs) (including HIV) and of high-risk sexual behaviour in the following three groups: primary infertile relationships, secondary infertile relationships and fertile relationships. Primary infertility is here defined as never having conceived before, secondary infertility as infertility subsequent to having conceived at least once. Design: Unmatched case–control study. Methods: Sexually active infertile women aged 21–45 years presenting at an infertility clinic of the Kigali Teaching Hospital, Rwanda and their male partners were invited to participate. Fertile controls who had recently delivered were recruited from the community. In a face-to-face interview, participants were asked about sociodemographic characteristics and their sexual behaviours, and tested for HIV and STIs. Results: Between November 2007 and May 2009, 312 women and 254 partners in infertile relationships and 312 women and 189 partners in fertile relationships were enrolled. Involvement in a secondary infertile relationship was associated with HIV infection after adjusting for sociodemographic covariates for women (adjusted OR (AOR)=4.03, 95% CI 2.4 to 6.7) and for men (AOR=3.3, 95% CI 1.8 to 6.4). Involvement in a primary infertile relationship, however, was not. Secondary infertile women were more likely to have engaged in risky sexual behaviour during their lifetime compared with primary infertile and fertile women. Men in primary and secondary infertile relationships more often reported multiple partners in the past year (AOR=5.4, 95% CI 2.2 to 12.7; AOR=7.1, 95% CI 3.2 to 15.8, respectively). Conclusions: Increased HIV prevalence and risky sexual behaviour among infertile couples is driven by secondary infertility. Infertile couples, and especially those with secondary infertility, should be targeted for HIV prevention programmes and their fertility problems should be addressed.